The global burden of climate-sensitive diseases in Brazil: the national and subnational estimates and analysis, 1990–2017 - Tatiane C. Moraes de Sousa; Christovam Barcellos; Mauricio L. Barreto (Population Health Metrics)
Abstract Background Climatic factors have been associated with the occurrence of several diseases known as climate-sensitive diseases (CSDs). We selected the following categories of disease to represent CSDs for this study: vector-borne diseases (dengue, leishmaniasis, malaria, schistosomiasis, yellow fever, and zika), infectious-diseases (respiratory infections), non-communicable diseases (chronic respiratory and cardiovascular diseases) and water-borne diseases (diarrhea). This study aimed to describe the historical trends and spatial distribution of mortality and morbidity of these selected Climate Sensitive Diseases in Brazil between 1990 and 2017. The analysis is based on findings obtained by the 2017 Brazilian Global Burden of Diseases (GBD) Study. Methods Yearly CSD data was taken from the 2017 Brazilian GBD Study for the years between 1990 and 2017. This data was organized by age group and sex at the country level, for 26 states and one Federal District (known as Federative Units), and at the regional level. Results Cardiovascular and respiratory diseases presented the greatest disability adjusted life-years (DALYs) in Brazil, followed by chronic and infectious respiratory diseases, although only a small fraction could be attributed to climate changes. Among the vector-borne diseases, the burden of leishmaniasis and malaria have decreased since 1990, while the burden of dengue has increased. The burden of other vector-borne diseases (malaria and yellow fever) increased since 2015, in addition to the recent introduction of zika virus in Brazil. The GBD rates of infectious diseases were greater in predominately the Amazon and northeast regions. This finding contrasts with dengue and zika for which an increase in DALYs rate was observed southeast and central-west, besides the northeast region. The lowest DALYs rates for dengue were observed in the south region, which also experiences the lowest temperatures. Conclusions The burden of CSDs in Brazil has increased since 1990 considering non-communicable and communicable diseases. The potential impact of climate change on such diseases must be evaluated considering disease dynamics and spatial specificities, such as land cover and climate patterns. The main challenges in Brazil related to CSDs are the investments needed for research regarding the increase in the burden of CSDs, for vector control and social health determinants mitigation.